2015
DOI: 10.1080/02640414.2015.1012102
|View full text |Cite
|
Sign up to set email alerts
|

Performance of gymnastics skill benefits from an external focus of attention

Abstract: The present study was designed to fill a gap in the literature on attentional focus and sports performance. Specifically, in contrast to most previous studies in which an external focus was directed at an implement, we used a gymnastics skill that did not involve the use of an implement. Furthermore, while most studies used only outcome measures of performance, we also assessed movement quality. Twelve-year-old gymnasts performed a maximum vertical jump with a 180-degree turn while airborne, with their hands c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
65
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 36 publications
7
65
2
4
Order By: Relevance
“…Expert ratings (Abdollahipour, Wulf, Psotta, & Palomo Nieto, 2015;Wulf, Chiviacowsky, Schiller, & Ávila, 2010) as well as analyses of movement kinematics (An, Wulf, & Kim, 2013;Christina & Alpenfels, 2014;Lohse, Sherwood, & Healy, 2010;Parr & Button, 2009;Southard, 2011;Wulf & Dufek, 2009) have shown that movement form can be optimized with external relative to an internal focus as well. For example, in novice rowers, instructions directed at the blade (e.g., "Keep the blade level during the recovery") rather than the hands (e.g., "Keep your hands level during the recovery") led to greater improvements in the technique, as evidenced by various kinematic measures after a 7-week retention interval (Parr & Button).…”
Section: Movement Formmentioning
confidence: 99%
“…Expert ratings (Abdollahipour, Wulf, Psotta, & Palomo Nieto, 2015;Wulf, Chiviacowsky, Schiller, & Ávila, 2010) as well as analyses of movement kinematics (An, Wulf, & Kim, 2013;Christina & Alpenfels, 2014;Lohse, Sherwood, & Healy, 2010;Parr & Button, 2009;Southard, 2011;Wulf & Dufek, 2009) have shown that movement form can be optimized with external relative to an internal focus as well. For example, in novice rowers, instructions directed at the blade (e.g., "Keep the blade level during the recovery") rather than the hands (e.g., "Keep your hands level during the recovery") led to greater improvements in the technique, as evidenced by various kinematic measures after a 7-week retention interval (Parr & Button).…”
Section: Movement Formmentioning
confidence: 99%
“…Instead, Abdollahipour et al (2015) 67 focus discussion on theory and laboratory/fundamental research findings (e.g., Kal, van der 68 Kamp, & Houdijk, 2013;Land, Frank, & Schack, 2014;Wulf, Höß, & Prinz, 1998) Indeed, elite-level athletes report beneficial effects from focussing on aspects of the 88 movement (e.g., Bernier, Trottier, Thienot, & Fournier, 2015;Carson, Collins, & 89 MacNamara, 2013;MacPherson, Collins, & Morriss, 2008;Nyberg, 2015;Orlick & 90 Partington, 1988;Robazza & Bortoli, 1998) and, sport psychologists often employ explicit 91 movement imagery techniques to enhance competitive performance (e.g., Carson,Collins,& 92 Jones, 2014; Collins, Morriss, & Trower, 1999;Martindale & Collins, 2012;Wang & Zhang, 93 2015). Accordingly, failure to contextualise the study within current coaching/sport 94 psychology practices, or to explain why athletes' perceptions are apparently wrong, surely 95 limits the paper's ability to serve its purpose in a purportedly applied discipline.…”
mentioning
confidence: 98%
“…Letter to the editor concerning the article "Performance of gymnastics skill benefits from an 48 external focus of attention" by Abdollahipour, Wulf, Psotta & Nieto (2015) …”
mentioning
confidence: 99%
See 2 more Smart Citations